Opportunities for Towani Tolotang Women in the Public Sphere (Martabat: Jurnal Perempuan dan Anak, 2023)
The Towani Tolotang community is known to be highly egalitarian and emancipative. Towani Tolotang society isopen to having leaders. Towani Tolotang women are allowed to be involved in public activities. This study aims to examine the possibilities of Towani Tolotang women in Sidrap Regency within the scope of customs that form the basis of their strength to participate in the public sphere. This study uses a qualitative research method with a descriptive type to explain the results obtained from interviews that are analyzed factually, objectively,and systematically. This research shows that the customary rules in the Towani Tolotang community in Sidrap Regency do not differentiate between male and female gender. All parties are entitled to hold the position of ordinary leader based on their lineage and character. Based on this, the patriarchal culture of Bugis society does not affect the status of women in Towani Tolotang society, giving women in Towani Tolotang society theopportunity to participate in the public sphere.